2004
DOI: 10.1176/appi.ps.55.5.581
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Episodes of Seclusion and Restraint in a Psychiatric Emergency Service

Abstract: The authors developed a comprehensive plan focusing on the early identification and management of problematic behaviors in an effort to reduce seclusion and restraint in a psychiatric emergency service and to increase adherence to hospital standards for its use. Hospital data for nine months before and nine months after the implementation of the plan were retrospectively reviewed. Two key factors that were believed to increase the likelihood of episodes of seclusion and restraint were ineffectual management of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 6 publications
0
48
0
Order By: Relevance
“…For example, one study of a hospital in New York reported reductions in restraint/seclusion despite the 'one hour rule' (reassessment of a patients within one hour of initiating restraint or seclusion) and other regulations being in place for some time before a range of interventions were introduced (26). In another study, JCAHO standards were introduced in the middle of the study period, but did not appreciably contribute to the already reduced levels of restraint/seclusion episodes (27). However, the way in which policy changes translate into practice was not examined by these studies.…”
Section: Changes In State or Local Policymentioning
confidence: 99%
“…For example, one study of a hospital in New York reported reductions in restraint/seclusion despite the 'one hour rule' (reassessment of a patients within one hour of initiating restraint or seclusion) and other regulations being in place for some time before a range of interventions were introduced (26). In another study, JCAHO standards were introduced in the middle of the study period, but did not appreciably contribute to the already reduced levels of restraint/seclusion episodes (27). However, the way in which policy changes translate into practice was not examined by these studies.…”
Section: Changes In State or Local Policymentioning
confidence: 99%
“…Extensive efforts have been made in Europe and America over the past decade to assess rates of coercive measures systematically [1][2][3] and to reduce them [4]. D'Orio et al [5], for example, report a 39% reduction in coercion following introduction of a package which included enhanced access to expertise during emergency situations. Involvement in the use of these measures or witnessing their use can be highly distressing for both service users and staff [6][7][8] and few are likely to remain neutral about them.…”
Section: Introductionmentioning
confidence: 99%
“…The use of counselling/de-escalation is reflective of the value placed on this method, which is regarded as a core skill of nursing staff in reducing the use of restrictive measures (D'Orio, Purselle, Stevens, & Garlow, 2004). The information on PRN use in the present study is important, given the lack of data in this area and questions regarding its efficacy in managing aggressive and disturbed behaviour (Delaney, 2006).…”
Section: Resultsmentioning
confidence: 98%